Increasing Expression of PnGAP and PnEXPA4 Provides Insights Into the Enlargement of Panax notoginseng Root Size From Qing Dynasty to Cultivation Era - Yu, Mu-Yao; Hua, Zhong-Yi; Liao, Pei-Ran; Zheng, Han; Jin, Yan; Peng, Hua-Sheng; Cui, Xiu-Ming; Huang, Lu-Qi; Yuan, Yuan (Frontiers in Plant Science, 2022)
Root size is a key trait in plant cultivation, and can be influenced by cultivation environment. However, physical evidence of root size change in a secular context is scarce due to the difficult preserve of ancient root samples, and how they were modified during the domestication and cultivation stays unclear. 100 ancient root samples of Panax notoginseng preserved as tribute in Palace Museum (A.D. 1636 to 1912, Qing dynasty), provided an opportunity to investigate the root size changes during the last 100 years of cultivation. The dry weight of ancient root samples (~120 tou samples, tou represents number of roots per 500g dry weight) is 0.22-fold of the modern samples with the biggest size (20 tou samples). Transcriptome analysis revealed that PnGAP and PnEXPA4 were highly expressed in 20 tou samples, compared with the 120 tou samples, which might contribute to the thicker cell wall and higher content of lignin, cellulose as well as callose in 20 tou samples. A relatively lower content of dencichine and higher content of ginsenoside Rb1 in 20 tou samples, is also consistent with higher expression of ginseosides biosynthesis related genes. The expression of PnEXPA4 has a significantly positive correlation with the transcriptional level of GGPPS, suggesting a relation between cell wall architecture and ginsenoside biosynthesis. PnPHL8 was filtrated through transcriptome analysis, which could specifically bind the promoters of PnGAP, PnCYP716A47 and PnGGPPS, respectively. The results in this study represent the first physical evidence of root size changes of P. notoginseng in the last 100 years of cultivation, and contribute to a comprehensive understanding of how cultivation environment affected root size, chemical composition and clinical application.